Sustainability Status of Small-Scale Capture Fisheries in Raja Ampat Regency (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
The small-scale capture fisheries sector is vital to the economy of Raja Ampat Regency. Still, it faces sustainability challenges, including ecological pressures, limited access to technology, low welfare among fishers, and weak governance. The objective of this study is to evaluate the sustainability status of small-scale capture fisheries in Raja Ampat based on five dimensions: economic, ecological, social, technological, and legal and institutional. The Rapid Appraisal for Fisheries technique was employed to analyze sustainability in a multidimensional manner, followed by Monte Carlo and Leverage analysis to identify leverage attributes in each dimension. Results show that the ecological and economic dimensions are moderately sustainable, while the social, technological, and legal and institutional dimensions are less sustainable. Key leverage attributes include fish size, fishing time, and species variability in ecology; fisheries marketing, business capital, additional income, and subsidies in the economy; regulation compliance and fisher group roles in social aspects; selective fishing gear and quality management in technology; and law enforcement, rule dissemination, and institutional guidance in the legal and institutional dimension. Enhancing these attributes is expected to support the sector's sustainability in Raja Ampat.